Pembangunan dan Implementasi Sistem Informasi Bank Darah di PMI dan RSUD Muntilan Kabupaten Magelang - Agnes Maria Polina; Fenty Fenty (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
Blood bank administration in PMI, Magelang Regency is still managed manually, which prevents hospitals from accessing information on blood stock quickly. Hospitals can access information about blood stock by phone only. Such a manual system could be a problem in delivering an excellent service. Therefore, a solution is required to improve the quality of services delivered by PMI. The use of information technology called Blood Bank Information System (SIBD/Sistem Informasi Bank Darah) is promising to improve the quality of services of the PMI. The SIBD helps the hospital to improve time efficiency in the blood demand process. There were several activities which have been completed, i.e.: 1) Developing SIBD at PMI of Magelang Regency; 2) Improving hardware facilities at PMI of Magelang Regency and RSUD Muntilan, including the procurement of computer hardware, modem, and Internet access for each institution; 3) Training on the use of SIBD for both PMI and hospital staff. The results were: 1). SIBD at PMI which is linked to RSUD Muntilan and other hospitals for blood supply information and online order; 2) Blood Bank Administration Database which can improve quality of service; 3) capability of PMI and RSUD Muntilan, Magelang Regency staff in utilizing SIBD to improve services to patients.